Estimates for the best bilinear approximations of the classes $B^r_{p,θ}$ and singular numbers of integral operators - Romanyuk, A. S.; Romanyuk, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We obtain the exact-order estimates for the best bilinear approximations of the Nikol‘ski–Besov classes $B^r_{p,θ}$ of periodicfunctions of several variables. We also find the orders for singular numbers of the integral operators with kernels from theclasses $B^r_{p,θ}$.